Inappropriate antibiotic prescription for acute tonsillitis in low- and middle-income countries (LMICs): a systematic review and meta-analysis protocol - Emmanuel Choffor-Nchinda; Antoine Bola Siafa; Yves Christian Andjock-Nkouo (BMJ Open)
Introduction Tonsillitis is a self-limiting inflammatory process of the tonsils. In high-income countries, guidelines have been developed to decide if a patient needs an antibiotic or not. These guidelines help to reduce unnecessary antibiotic prescriptions and prevent the development of antimicrobial resistance (AMR). In low- and middle-income countries (LMICs), medical practitioners have the tendency to prescribe antibiotics in all cases of tonsillitis; there is an overprescription of antibiotics. These prescriptions are probably unjustified and seem to be responsible for the increased AMR seen in developing countries. The aim of this review will be to estimate the proportion of unjustified antibiotic prescriptions in LMICs.Methods and analysis We will conduct a systematic review of all observational studies on the diagnosis and treatment of tonsillitis in LMICs. The selected database will include PubMed, Web of Sciences Global Index Medicus and the Grey literature. The search will include studies published from January 2012 until December 2024. Study selection will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, and bias will be assessed by a Risk of Bias Assessment Tool for observational studies by Hoy et al. A meta-analysis will be conducted for homogeneous studies, eventually using the random effect model. Subgroup analysis will include a period of study, study quality, countries and/or subregions of LMICs involved, study setting, age of participants, tools and definition used.Ethics and dissemination Formal ethical approval is not required, as primary data will not be collected. The results will be disseminated through peer-reviewed publications and presented at scientific conferences.PROSPERO registration number CRD 42022384957